CAHAYA ILMU DARI ANDALUSIA: RELEVANSI SISTEM PENDIDIKAN UMAYYAH DI ERA KONTEMPORER - Tuti Kurnia; Salmi Wati (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The journey of Islamic education has always been in line with the various periods in the history of Islam itself. One of them is the development of education during the Umayyad Daulah in Andalusia. The purpose of this research is to find out the education system during the Umayyad period and its relation to Islamic education today. This type of research is librabry research or literature study sourced from literature in the form of journal articles, books, theses, and other sources. Literature in the form of journal articles, books, theses that discuss the education system during the Umayyad period. The results obtained from this study show that the education system during the Umayyad Dynasty had a good education system. The education system during the Umayyad Dynasty has a significant relevance to the contemporary era, especially in a holistic approach. The results obtained from this study indicate that the education system during the Umayyad Dynasty had significant relevance to the contemporary era, especially in the holistic and inclusive approaches applied.